Thermal stress thresholds and physiological response in seedlings of Abies hickelii (Flous & Gaussen), an endangered species - Hernández-Cruz, Iván (2026)
Abies hickelii is an endemic, endangered species that is highly sensitive to climatic fluctuations. Increasing drought and extreme temperature events may threaten its long-term survival. This study evaluated the thermal sensitivity of A. hickelii seedlings under controlled conditions. Individuals were exposed to four thermal treatments (control, 28 °C, 32 °C, and 36 °C), and both the time required to reach maximum thermal stress and the rate of foliar damage were assessed. Temperature explained more than 60% of the variability in the time to maximum stress. At 36 °C, seedlings exhibited the highest stress levels and a five-fold increase in damage rate compared to the control, indicating that a critical thermal threshold had been surpassed. Additionally, the progression of damage slowed after exceeding 90% foliar loss, suggesting the presence of a physiological inflection point. Although no significant differences were found among the control, 28 °C, and 32 °C treatments, smaller seedlings showed signs of greaterresistance. Overall, these results highlight the species’ high vulnerability to extreme heat events and provide essential information for guiding conservation and reforestation strategies under climate-change scenarios.